Evaluating Author Productivity and Journal Professionalism Using Lotka's Law - Cecep Ibrahim; Eka Suaib; Asrul Jaya; Moh. Ricky Ramadhan R.; Hera Pebrianti; Muthmainnah Aufaa Hamzah (BACA: Jurnal Dokumentasi dan Informasi, 2026)
Correction Note: The authorship list for this article has been updated to align with the official institutional research report. By mutual consent, Rahmat Fadhli has been removed from the list, while Asrul Jaya, Moh. Ricky Ramadhan R, Hera Pebrianti, and Muthmainnah Aufaa Hamzah have been added. This administrative correction does not affect the scientific integrity of the study. Corrected Author List: Cecep Ibrahim, Eka Suaib, Asrul Jaya, Moh. Ricky Ramadhan R, Hera Pebrianti, Muthmainnah Aufaa Hamzah. For detailed author contributions and the official signed declaration, please refer to the attached Authorship Change Consent Form. Lotka's law is a bibliometric approach that examines the authorship distribution. The study in Jurnal Ilmu Informasi Perpustakaan dan Kearsipan evaluated authors' productivity and professionalism in three ways using Lotkas' law: straight count, complete count, and proportionate count. This study involved data collection, cleaning, and extraction, as well as data analysis. Data are collected directly from the Jurnal Ilmu Informasi Perpustakaan dan Kearsipan. Data cleaning and extraction are necessary to ensure data veracity. The third stage involves data analysis using straight, complete, and proportionate count processes along with Lotka's law. The results show that the calculation using the straight count follows Lotka's law, whereas the complete count does not. This journal is unprofessional. The use of straight count and complete count will agree with Lotka's proposition if journal management is done properly. Suggestions for further research: Lotka's law technique can be used to assess a journal's professionalism in terms of article publication and dissemination.